FAKTOR PENOLAKAN PERKEBUNAN KELAPA SAWIT MASYARAKAT DI KECAMATAN SIBERUT TENGAH KABUPATEN KEPULAUAN MENTAWAI - Nurhayati, Sri Ramdaya; Rianto, Slamet; Yuherman, Yuherman (Pendidikan Geografi, 2013)
This study aimed to determine the rejection of oil palm plantations in the Central District of Siberut Mentawai Islands.Type of research is descriptive. The population is all the families who reside in the Central District of Siberut. Based on recent data the population of 950 inhabitants with 218 households. Respondent sample taken with the technique of random sampling proportional to the proportion of 20 % so that the sample was 68 families.The research found that : 1) cultural factors are the main causes of the rejection of oil palm plantations in the Central District of Siberut, because ownership of communal land is generally owned by indigenous elders, culture is still strong and the workers have not been able to adapt to the culture of the surrounding community, (2) livelihood factor is the cause of the oil palm rejection because people rarely get jobs related to the oil palm plantation dai Middle Siberut, (3) the level of income of the people in the Middle District of Siberut is generally low , but is able to meet the basic needs of the family, and (4) level of public education in the District of Central Siberut is low, generally graduated junior high